The millipede genus Leucogeorgia Verhoeff, 1930 in the Caucasus, with descriptions of eleven new species, erection of a new monotypic genus and notes on the tribe Leucogeorgiini (Diplopoda: Julida: Julidae) - Antić, Dragan Ž.; Reip, Hans S. (European Journal of Taxonomy, 2020)
The Caucasian leucogeorgiinine genera Archileucogeorgia Lohmander, 1936 and Leucogeorgia Verhoeff, 1930 are revised, with Leucogeorgia being considered as a senior subjective synonym of Archileucogeorgia, syn. nov. The following new combinations are thus warranted: Leucogeorgia abchasica (Lohmander, 1936) and L. satunini (Lohmander, 1936), both comb. nov. ex Archileucogeorgia. All four previously described species, viz., L. longipes Verhoeff, 1930, L. abchasica, L. satunini and L. rediviva Golovatch, 1983, are redescribed based on new material, partly also on the type series, with a lectotype being designated for L. longipes. In addition, eleven new species of Leucogeorgia are described, both with normal (L. borealis sp. nov., L. gioi sp. nov., L. golovatchi sp. nov., L. lobata sp. nov., L. oculata sp. nov. and L. prometheus sp. nov.) and modified mouthparts (L. caudata sp. nov., L. mystax sp. nov., L. profunda sp. nov., L. redivivoides sp. nov. and L. turbanovi sp. nov., all clearly troglobionts). Additionally, a new monotypic genus, Martvilia gen. nov., is erected, with M. parva gen. et sp. nov. as the type species, another presumed troglobiont. An identification key to both genera and all 16 species of Caucasian Leucogeorgiini is presented. Several other members of this tribe are also re-examined, including a syntype male of Telsonius nycteridonis Strasser, 1976, from Greece, herewith designated as the lectotype. Troglomorphisms and mouthpart modifications, as well as the distributions and relationships within both Leucogeorgia and Leucogeorgiini, and a Leucogeorgiini species richness estimate for the western Caucasus are discussed.